The Effect of Corporate Governance on Tax Avoidance (Empirical Study of the Consumer Goods Industry Companies Listed On Indonesia Stock Exchange Period 2013-2016) - Dina Marselawati, Kartika Hendra Titisari & Endang Masitoh (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Tax avoidance is the steps taken by a person to avoid taxes but in legal ways. Thistax evasion can be said to be a complicated and unique issue because on the onehand it is permissible, but not desirable. This study aims to examine and analyzethe effect of Corporate Governance on Tax Avoidance. Corporate Governance isproxied with institutional ownership, independent board of commissioners, auditcommittee, and audit quality, while Tax Avoidance is proxied by Cash EffectiveTax Rate. Population in this research is all of Consumer Goods Industry Companywhich listed in Indonesia Stock Exchange Year 2013-2016. The samplingtechnique used Purposive Sampling method. Purposive Sampling method obtainedby the sample of 19 companies. Data analysis method used in this research is usingmultiple linear regression analysis. Based on the results of model feasibility testing(F test) shows that the independent variables (institutional ownership, independentboard of commissioner, audit committee, and audit quality) have a significanteffect on the tax avoidance variable. Hypothesis testing (t test) shows that theinstitutional ownership and audit committee have an effect on Tax Avoidance,whereas independent board and audit quality have no effect on Tax Avoidance.keywords: Corporate Governance, Tax Avoidance.